As imagens da cultura política brasileira em A carteira de meu tio de Joaquim Manuel de Macedo - CARNEIRO JÚNIOR, Nelson (2008)
The novel A carteira de meu tio, written by Joaquim Manoel de Macedo, shows the reality of Brazilian political culture during 19th century. The book makes radiography of political customs, using symbols and allegories that re-affirm the image of country with a low consistence in representatives and institutional political space exiguous in function of predominance of privilege of clients. The allegories presented in the book A carteira de meu tio, refers to the constitution of 1824, are the starting point of this research that realizes a social interpretation of a literary work, showing how this one present important representations to analyzes of society. This essay intends to study how cultural aspects from national political culture presents in A carteira de meu tio are appropriated by literary representation and historical and social production. Literature is the support that will allow revealing the images elaborated by the author and through historical part and a social analyzes, we will show what exist besides the present speeches in literary work about the purpose of the research. The representation of the imperial constitution of 1824 in A carteira de meu tio, by Joaquim Manoel de Macedo, symbolizes and presents political practices realized in Second Empire Government and the images of political activity in Brazil The conception of political citizenship and the role taken by political institutions in the country during 1853 to 1865 are evaluated as decisive elements in consolidation of a national political culture.